Nutritional Disorders of Macronutrients in Bletia catenulata - de David, Carlos Henrique Oliveira; de Paiva Neto, Vespasiano Borges; Campos, Cid Naudi Silva; da Silva Liber Lopes, Priscilla Maria; Teodoro, Paulo Eduardo; de Mello Prado, Renato [UNESP] (American Society for Horticultural Science, 2019)
This study evaluated the impact of macronutrient omission on nutritional disorders and the in vitro growth of Bletia catenulata. The experiment was performed in a growth room, with a controlled environment, in the biotechnology laboratory of the Campus of Chapadão do Sul (CPCS/UFMS). The experiment consisted of a completely randomized design, with seven treatments and four replications, corresponding to the following treatments: complete treatment (N, P, K, Ca, Mg, S, B, Mn, Zn, Cu, Fe, and Mo), nitrogen omission (–N), phosphorus omission (–P), potassium omission (–K), calcium omission (–Ca), magnesium omission (–Mg), and sulfur omission (–S) in B. catenulata. After detecting the symptoms, plant height, leaf area, dry weight, micronutrient content in the shoot, micronutrient accumulation in the shoot, and visual symptoms of nutritional deficiency were evaluated. The –N, –P, –Ca, and –Mg treatments hindered plant growth and dry weight yield. The deficiency of each nutrient resulted in morphological changes, which were verified by typical visual symptoms of nutritional disorder for each nutrient.
Keywords: Nutritional disorder; Orchidaceae; Plant nutrition